Agency Theory and Foreclosure Sales of Properties - Chau, K. W.; Ng, R. C. K. (International Journal of Property Sciences (E-ISSN: 2229-8568), 2008)
This study analyze s the effect of foreclosure status on residential property price using Hong Kong data.Results of previous studies on the effect of foreclosure status on property price have been mixed. Some suggested that foreclosed properties are sold at a discount, while others provided contrary evidence. In this study, we propose that agency issues, which were ignored in previous studies, have an important role to play in determining the prices of foreclosed properties under different market conditions. When the market is booming, the mortgage loan on a property is likely to be lower than its marke t value. The bank’s objective is to sell the property as quickly as possible to recover the loan. The tradeoff between time -on-the-market and transaction price implies that foreclosed properties are sold at a discount to market prices. On the other hand, during market downturns, the mortgage loan is likely to be higher than the market value. The banks will have less incentive to trade time -on-the-market for price, and foreclosed properties are less likely to be sold at a discou1nt, and thus add bad debts into their books. Empirical results from Hong Kong suggest that that foreclosed properties are sold at a 10% discount in an up market, but are sold at no discount in a down market. The result s are consistent with our prediction. Keywords: Agency theory, foreclosure, hedonic price model, Hong Kong, residential properties